Informal Economy Sector as a Catalyst for Nigerian Economy Development and Sustainability: A Review - Michael Adelakun Balogun (Richtmann Publishing, 2022)
Informal economy sector is a major part of the global economy that provides the needed or alternative economy development approach for sustainability. This paper assessed the impacts of informal sector on the economy development of Nigerian and its challenges for sustainability. The Max Weber and Dudley Seers social developmental theory were used to explained the study, while some importance and challenges of the sector were explored. The paper therefore concluded that since informal economy sector can improve/encourage economic standard of individuals and reduce the focus from globalized to the local alternative path of development and sustainable future, it then recommends amongst other that processes should put in place to capture the dynamics of the sector and the best way to tap into its potential since it has the capacity to increase Nigerian economy predicament and beyond. Also, policy to support and to address the identified challenges towards improving the sustainability and productivity of the sector should made possible in Nigeria and other related international state. Received: 10 April 2022 / Accepted: 30 June 2022 / Published: 5 July 2022